(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Pal and Bhattacharyya (1996)introduced the notion of pre–open sets.In this paper, we consider the class of pre–open sets in topological spaces and investigate some of their properties. Also,we present and study some weak separation axiomsby involving the notion of pre–open sets.